OLDER AND LESS DEVIANT? A MEDIATED MODERATION MODEL OF AGE, COGNITIVE REAPPRAISAL, AND ABUSIVE SUPERVISION. (11th November 2018) - Peng, Y; Xu, X; Matthews, R
Abstract: Given the aging trend in the workforce, examining the risky and protective factors of older workers' work performance has important implications. The present study investigated the moderation effect of employee age on the relationships of abusive supervision with organizational and interpersonal deviance, as well as whether employees' use of cognitive reappraisal mediated these moderation effects. In a group of 615 occupational and physical therapists from the Midwestern United States, this study found that employee age significantly moderated the relationships of abusive supervision with both organizational and interpersonal deviance. Specifically, compared with younger workers, the effects of abusive supervision on organizational and interpersonal deviance were weaker among older workers. Furthermore, use of cognitive reappraisal significantly mediated these moderation effects. Findings suggest that habitual use of cognitive reappraisal may account for age-related advantages in responding to abusive supervision. Theoretical and practical implications are discussed.